2006
DOI: 10.1016/j.jappgeo.2005.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of thin sandy aquifers by using high resolution reflection seismics and 2-D electrical tomography

Abstract: Electrical tomography, which gives good results even in fairly complex geological environments, has given a new lease of life to electrical methods in hydrogeological surveys. Nevertheless, a rapid decline in resolution with increasing depth remains the main problem of the electrical methods. In the Pannonian basin in Croatia, at a test area, combining both electrical tomography and seismic reflection methods provides data that better constrain the lithological and hydrogeological model of the subsurface.Elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…The principal applications of this technique include (see for example Telford et al, 1990;Reynolds, 1997;Šumanovac, 2006) definition of aquifer boundary units, such as aquitards, bedrock, faults and fractures, the detection of voids in karstic regions, the mapping of saltwater intrusions into coastal aquifers, the identification of contaminated groundwater plumes, the detection of mineralized zones, and the exploration of sand and gravel resources among others.…”
Section: Electrical Resistivity Imaging (Eri)mentioning
confidence: 99%
“…The principal applications of this technique include (see for example Telford et al, 1990;Reynolds, 1997;Šumanovac, 2006) definition of aquifer boundary units, such as aquitards, bedrock, faults and fractures, the detection of voids in karstic regions, the mapping of saltwater intrusions into coastal aquifers, the identification of contaminated groundwater plumes, the detection of mineralized zones, and the exploration of sand and gravel resources among others.…”
Section: Electrical Resistivity Imaging (Eri)mentioning
confidence: 99%
“…This technique has numerous possible applications when one is faced with various problems in different geological settings (Caputo et al, 2003;Colella et al, 2004). It is increasingly used in environmental studies, hydrogeology (Maillet et al 2005;Š umanovac, 2006;Martínez et al, 2009), and geotechnics (Naudet et al, 2008), among other fields. This technique has also been used for detection of natural crevice-type caves (van Schoor, 2002;Gutiérrez et al, 2009;Pá nek et al, 2010;Gambetta et al, 2011) and in some cases, to locate manmade mining cavities (Maillol et al, 1999;Martínez-Ló pez et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…) or the application of other geophysical methods (seismic reflection and refraction, gravity) to validate the results obtained. Some recent works have shown that the application of resistivity methods can reveal very important details of the weathered zones, the hydrological system, and geological structure (Robain et al, 1996;Lebourg et al, 1999;Ritz et al, 1999;Jongmans et al, 2000;Sumanovac and Weisser, 2001;Lebourg and Frappa, 2001;Godio and Bottino, 2001;Wise et al, 2003;Perrone et al, 2004;Lebourg et al, 2005;Rey et al, 2006;Godio et al, 2006;Sumanovac, 2006). However, this method has been rarely used on deep seated landslides because of logistical difficulties with using resistivity equipment in steep and unstable terrain.…”
Section: Introductionmentioning
confidence: 99%